Cattle importation in relation to occurrence of foot and mouth disease in Peninsular Malaysia - Abdullah, Ummi Noorhakimah (2014)
Foot and Mouth Disease (FMD) in Peninsular Malaysia continue to be a challenge for the cattle industry. FMD is a transboundary disease and considered as one of the most contagious disease among domestic and wild cloven-hoofed animals. The disease causes a significant negative economical impact throughout Peninsular Malaysia through production losses and inaccessible export market. Malaysia has been highly dependent on cattle importation to increase the live cattle population and to maintain adequate beef and milk supply. Importation and movement of animals have been constantly linked to FMD outbreaks. This study aimed to find the relation between the importation of live cattle and its contribution to the FMD occurrences in Peninsular Malaysia. The specific objectives of the study were to: describe the cattle importation trends and statistics from year 2000 to 2010 and to suggest its relationship with the local FMD occurrences within the same time frame, describe the import protocol for cattle imposed by the veterinary authority of Malaysia, the Department of Veterinary Services (DVS) so as to achieve a better understanding on the procedure and to identify the presence of gaps or weaknesses that may contribute to the FMD occurrence among local animals and describe the distribution of the government animal quarantine stations (GQS) and temporary animal quarantine stations (TQS) in Malaysia for the year 2012-2013 and to examine the temporary quarantine station’s managers awareness on the requirements and procedures for quarantine stations. Between 2004 and 2006, the numbers of live cattle imported to Peninsular Malaysia markedly decreased due to the suspension of cattle importation from Thailand by the DVS, Malaysia following several outbreaks of FMD from cattle consignments received in this country. The increase in the volume of cattle imported between 2007 and 2009 appeared to be consistent with the marked increase of FMD outbreaks within the same time frame. The study also found that several consignments between 2009 and 2010 contained cattle that were non-structural protein (NSP) positive indicating subclinical infection or previous exposure to the virus. The findings suggested that importation and animal movements are indeed contributors of FMD outbreaks in the country. The cattle import protocol has been developed by the DVS according to the Office International Epizootics (OIE) recommendations in the Terrestrial Codes. DVS import protocols are established to complement the efforts of FMD control in the country and also to prepare Malaysia towards achieving FMD free status by year 2016. This study examined relevant official documentations and limited accessible data from various sources in order to describe and highlight potential issues in the import protocols in Malaysia. The study focused on the protocols for cattle imported from Thailand and Australia because these two countries are the largest live cattle exporter to Malaysia. The study found that DVS import protocols contains potential discrepancies from the recommendation by the OIE that could increase the risk of disease importation via cattle consignments. The quarantine period of 10 days recommended at the local quarantine station as opposed to 14 days as recommended by the OIE could result in animals with longer incubation period to be released among the local cattle herds and spread the infection. In addition, the level of compliance to the DVS import protocols among the exporters especially from Thailand was poor. Laboratory serological findings from quarantined cattle discovered evidence that trivalent FMD vaccination as required by the import protocol was not performed. In a consignment of cattle received in 2012, 84% of the cattle within the consignment had less than 50 percent inhibition (PI) for serotype A, 32.3% had less than 50 PI for serotype Asia 1 and 11.7% had less than 50 PI for serotype O. Another consignment had 2.5% cattle with less than 50% PI for serotype O, 84% had less than 50% PI for serotype A and 12% cattle had less than 50% PI for serotype Asia 1. This indicated possibilities that monovalent or bivalent vaccine was used instead of trivalent or the trivalent vaccine used was not potent. The activities and management of the animal quarantine stations can be a good indicator of the level by which disease can be prevented from entering the country. Eight temporary quarantine station (TQS) were selected and visited with the aim of assessing the awareness of managers and operators on the biosecurity requirements for quarantine station stated in Arahan Prosedur Tetap Veterinar Malaysia (APTVM) Pendaftaran Stesen Kuarantin Haiwan Sementara 2011 (SKH(S)). On average, 11.8% of the managers ignored the importance of biosecurity and operational requirement. On the other hand, 82.5% of them were confident that they had a good level of biosecurity and operational knowledge. A quarter (25%) of the respondents agreed that they did not have a good knowledge on how to manage a TQS. More than 37% did not understand the requirements based on the APTVM SKH(S). In addition, 25% did not have any systematic importation documentation and records while more than 37% were not aware that the consignment proven to be exposed to FMD could only be released to the DVS approved destination. In conclusion, it was suggested that importation and animal movements are major contributors to the FMD outbreaks in the country. Issues and gaps in the import protocols and regulations may result in increase risk of FMD introduction. TQS which was allowed for reasons to improve animal quarantine efficiency may in fact contribute to more damage since the study found that most facilities had poor biosecurity, did not comply with basic infrastructure requirements and station operators/managers have poor level of understanding about basic quarantine station management and operations.